Pengaruh Pengungkapan Indeks Good Corporate Governance, Return On Equity dan Leverage Terhadap Price To Book Value Pada Perusahaan Yang Terdaftar di Bursa Efek Indonesia - Awim Abdul (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2015)
This research aims to examine the influence of Good Corporation Governance perception index (GCGPI), Return On Equity and Leverage Ratio (Debt to Equity Ratio) to Price to Book Value of stock. This research sample used the Listing Company in Indonesian Stock Exchange and has been implementing and surveyed GCGPI period of 2010 until 2012 with consistent and regularly. Variables used are Good Corporate Governance Perception Index, ROE and Leverage Ratio as Independent variables and Price to Book Value of Stock as dependent variable. The analysis method used statistical method which was multiple regression analysis, F test and t test. F test was used to analysis simultaneous influence of independent variables to dependent variable. T test was used to analysis the partial influence of independent variables to dependent variable. The result of this research shows that GCGPI has negative influence to PBV in level confidence 90% and level of tolerance 10%, Level of significance = 0.057 and level of Beta = -0,246, ROE has not significant influence to PBV with level of significance = 0.359, LR (DER) has positive and significance influence to PBV with the level of significance = 0,000 . Base the analysis result GCGPI, ROE and LR (DER) with simultaneous influence to PBV.